Dynamics of the rice blast fungal population in the field after deployment of an improved rice variety containing known resistance genes - Wang, Wenjuan; Su, Jing; Chen, Kailing; Yang, Jianyuan; Chen, Shen; Wang, Congying; Feng, Aiqing; Wang, Zonghua; Wei, Xiaoyan; Zhu, Xiaoyuan; Lu, Guodong; Zhou, Bo (Scientific Societies, 2021)
Rice blast, caused by the fungus Magnaporthe oryzae, is one of the most destructive diseases of rice worldwide. Management through the deployment of host resistance genes would be facilitated by understanding the dynamics of the pathogen’s population in the field. Here, to investigate the mechanism underlying the breakdown of disease resistance, we conducted a six-year field experiment to monitor the evolution of M. oryzae populations in Qujiang from Guangdong. The new variety of Xin-Yin-Zhan (XYZ) carrying R genes Pi50 and Pib was developed using the susceptible elite variety, Ma-Ba-Yin-Zhan (MBYZ), as the recurrent line. Field trials of disease resistance assessment revealed that the disease indices of XYZ in 2012, 2013, 2016, and 2017 were 0.19, 0.39, 0.70, and 0.90, respectively, indicating that XYZ displayed a very rapid increase of disease severity in the field. To investigate the mechanism underlying the quick erosion of resistance of XYZ, we collected isolates from both XYZ and MBYZ for pathogenicity testing against six different isogenic lines. The isolates collected from XYZ showed a similar virulence spectrum across four different years whereas those from MBYZ showed increasing virulence to the Pi50 and Pib isogenic lines from 2012 to 2017. Molecular analysis of AvrPib in the isolates from MBYZ identified four different AvrPib haplotypes, i.e., AvrPib-AP1-1, AvrPib-AP1-2, avrPib-AP2, and avrPib-AP3, verified by sequencing. AvrPib-AP1-1 and AvrPib-AP1-2 are avirulent to Pib whereas avrPib-AP2 and avrPib-AP3 are virulent. Insertions of a Pot3 and an Mg-SINE were identified in avrPib-AP2 and avrPib-AP3, respectively. Two major lineages based on rep-PCR analysis were further deduced in the field population, implying that the field population is composed of genetically related isolates. Our data suggest that clonal propagation and quick dominance of virulent isolates against the previously resistant variety could be the major genetic events contributing to the loss of varietal resistance against rice blast in the field.